2021
DOI: 10.3389/fphar.2021.680400
|View full text |Cite
|
Sign up to set email alerts
|

An Update on the Effects of Probiotics on Gastrointestinal Cancers

Abstract: Because of their increasing prevalence, gastrointestinal (GI) cancers are regarded as an important global health challenge. Microorganisms residing in the human GI tract, termed gut microbiota, encompass a large number of living organisms. The role of the gut in the regulation of the gut-mediated immune responses, metabolism, absorption of micro- and macro-nutrients and essential vitamins, and short-chain fatty acid production, and resistance to pathogens has been extensively investigated. In the past few deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 215 publications
(116 reference statements)
0
3
0
Order By: Relevance
“…When it comes to probiotics and the benefits of taking them, Lactic acid bacteria (LAB) and Bifidobacteria are the first type of bacteria that comes to mind; however, some other yeasts and bacilli may be considered probiotics as well. Next to the protective roles against pathogenic microorganisms, it now becomes clear that probiotics could also trigger the immune surveillance against any malignancies through modulating anti-inflammatory, immune responses or interacting with cytotoxic lymphocytes Treg [54,57,[59][60][61][62]. There is a general point of view that probiotic bacteria could be used as a tool to modulate the microbiota and potentiate gut barrier function, thereby preventing cancer development and progression [63,64].…”
Section: Probiotics; a Solution To Prevent Gi Cancer Or A Magic Wand ...mentioning
confidence: 99%
“…When it comes to probiotics and the benefits of taking them, Lactic acid bacteria (LAB) and Bifidobacteria are the first type of bacteria that comes to mind; however, some other yeasts and bacilli may be considered probiotics as well. Next to the protective roles against pathogenic microorganisms, it now becomes clear that probiotics could also trigger the immune surveillance against any malignancies through modulating anti-inflammatory, immune responses or interacting with cytotoxic lymphocytes Treg [54,57,[59][60][61][62]. There is a general point of view that probiotic bacteria could be used as a tool to modulate the microbiota and potentiate gut barrier function, thereby preventing cancer development and progression [63,64].…”
Section: Probiotics; a Solution To Prevent Gi Cancer Or A Magic Wand ...mentioning
confidence: 99%
“…Different species of Lactobacillus inhibit the production of interleukin-8 and interferon gamma, attenuating inflammation in gastric epithelial cells and inhibit the adhesion of the bacterium H. pylori , linked to the initiation of gastric and colorectal cancer. ( Davoodvandi et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…B. longum and L. acidophilus treatment of Barrett’s esophagus cells downregulated the expression of caudal type homeobox 1, cyclooxygenase-2, tumor necrosis factor α, and phosphoprotein. 53, while the expression level of Interleukin-18 was enhanced, inhibiting the proliferation of cancer cells ( Davoodvandi et al, 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It includes using antioxidants, agents that lower the cholesterol, and mineral supplements [8]. In recent times, limited studies (mainly on animals) have also concluded that expenditure of probiotics can improve the metabolic profiles [9]. But these effects were noticed on animals and non-diabetic models.…”
Section: Introductionmentioning
confidence: 99%